Aplikasi Smart Home Untuk Mengaktifkan Lampu - Henti Nuraini Napitupulu; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Smart Home or Smart Home is a household control system that works and is controlled with the help of a computer, to integrate and control one or more household electronic devices automatically. With the aim of designing a prototype of a smart home control and monitoring system in the form of a prototype to control devices such as tv, fans, lights and website-based air conditioners that can be accessed using a Wireless Local Area Network (WLAN) which is expected to make it easier for users. The working system of this research is to simulate the control carried out by residents of the house by turning on or off electronic equipment using a smartphone as a tool to control Arduino as a microcontroller to give commands to the relay as a power regulator for electronic devices that are connected to an electrical connection. The Smarthome application will display the condition of the electronic device on or off. The advantage of the Smarthome application is that it does not require a webserver and internet network as a medium for sending data to Arduino for data storage media for electronic status on or off. After this research is completed, some conclusions can be drawn as follows: The test results of the circuit on the electronic device are successful. If the L1 button is pressed, L1 is on and the interface will turn red. If the L2 button is pressed, L2 is on and the interface will turn green. If the L3 button is pressed, L3 is on and the interface will turn yello. If the L4 button is pressed, L4 is on and the interface will turn blue.Keywords: Smart Home,WLAN, Arduino, webserver